Suicide ideation and behaviours after STN and GPi DBS surgery for Parkinson's disease: results from a randomised, controlled trial. Issue 10 (10th May 2013) - Weintraub, Daniel; Duda, John E; Carlson, Kimberly; Luo, Ping; Sagher, Oren; Stern, Matthew; Follett, Kenneth A; Reda, Domenic; Weaver, Frances M; ,
Abstract : Background: The risk of suicide behaviours post–deep brain stimulation (DBS) surgery in Parkinson's disease (PD) remains controversial. We assessed if suicide ideation and behaviours are more common in PD patients (1) randomised to DBS surgery versus best medical therapy (BMT); and (2) randomised to subthalamic nucleus (STN) versus globus pallidus interna (GPi) DBS surgery. Methods: In Phase 1 of the Veterans Affairs CSP 468 study, 255 PD patients were randomised to DBS surgery (n=121) or 6 months of BMT (n=134). For Phase 2, a total of 299 patients were randomised to STN (n=147) or GPi (n=152) DBS surgery. Patients were assessed serially with the Unified Parkinson's Disease Rating Scale Part I depression item, which queries for suicide ideation; additionally, both suicide behaviour adverse event data and proxy symptoms of increased suicide risk from the Parkinson's Disease Questionnaire (PDQ-39) and the Short Form Health Survey (SF-36) were collected. Results: In Phase 1, no suicide behaviours were reported, and new-onset suicide ideation was rare (1.9% for DBS vs 0.9% for BMT; Fisher's exact p=0.61). Proxy symptoms of relevance to suicide ideation were similar in the two groups. Rates of suicide ideation at 6 months were similar for patients randomised to STN versus GPi DBS (1.5% vs 0.7%; Fisher's exact p=0.61), but several proxy symptoms were worse in the STN group. Conclusions: Results from the randomised, controlled phase of a DBS surgery study in PD patients do not support a direct association between DBS surgery and an increased risk for suicide ideation and behaviours.